Employee Determination Decision Support System at Pt. Pos Indonesia in Medan using the TOPSIS Method (Case Study: Mail Processing Center Office) - Suryani Sianipar (International Journal of Basic and Applied Science, 2019)
TOPSIS method is widely used to solve practical decision problems. the concept is simple and easy to understand, computationally efficient and has the ability to measure the relative performance of decision alternatives in a simple mathematical form. in this case the alternative in question is the determination of the right employees to run as a consideration that the company can improve based on the criteria of employees at PT. Pos Indonesia Medan. With this method, it is hoped that the assessment will be more precise because it is based on the criteria and weights that have been determined so that it will get more accurate results for the determination of employees to be carried out. This thesis will describe the decision support system for determining employees at PT.